Rancang Bangun Sistem Kendali Otomatis Untuk Pengaturan Kecerahan Lampu Tidur Berbasis Android - Aldi Agustian; Muhammad Sabri; Akbar Wahyu Ananda; Sinek Mehuli Br PA (Institut Teknologi dan Bisnis Indonesia, 2026)
Automatic control systems have become an inevitable necessity in facilitating various aspects of daily life, where these systems allow their users to automate many processes that were previously done manually.Along with the rapid development of technology, the need for automation systems is increasing in various aspects of life, including in lighting arrangements at home. Proper lighting settings not only provide comfort, but can also affect the quality of sleep and health of its occupants.By considering these things, this study aims to develop a night light whose brightness can be adjusted according to the user's wishes without having to get out of bed, just with a few touches on the smartphone screen using a specially designed application and the application is easy to use. This research was conducted to develop a night light using Arduino as its main system, and to create an Android-based application that runs and regulates the brightness system of this night light. The author hopes that the design of this tool can be developed to be more sophisticated, better, and have more benefits and usefulness for its users